1979
DOI: 10.1097/00004032-197908000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Review of Report by Mancuso, Stewart and Kneale of Radiation Exposure of Hanford Workers

Abstract: An analysis of the Hanford data adjusted for age and calendar year of death reduces the number of cancer sites for which a radiation dose relationship can be suggested to two, cancer of pancreas and multiple myeloma. There is no suggestion of a radiation relationship for lymphatic and haemopoietic cancers other than myeloma, or for solid tumors of sites other than the pancreas, with the possible, and very weak, exception of the kidney. The conclusion of Mancuso et al. with regard to variations in sensitivity t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1981
1981
1993
1993

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…23 Elsewhere, in a retrospective telephone survey, six of 44 men with multiple myeloma acknowledged having had radiation exposure, whereas only three of 120 controls recalled prior radiation exposure.24 In the same study, six of 45 women with multiple myeloma and three of 108 female controls recalled prior radiation exposure. The influence of radiation on induction of multiple myeloma has been reviewed recently.2' Radiation does not appear to have had a part in our cases because there was no known exposure at work and none was documented in the homes.…”
Section: Environmentalmentioning
confidence: 99%
“…23 Elsewhere, in a retrospective telephone survey, six of 44 men with multiple myeloma acknowledged having had radiation exposure, whereas only three of 120 controls recalled prior radiation exposure.24 In the same study, six of 45 women with multiple myeloma and three of 108 female controls recalled prior radiation exposure. The influence of radiation on induction of multiple myeloma has been reviewed recently.2' Radiation does not appear to have had a part in our cases because there was no known exposure at work and none was documented in the homes.…”
Section: Environmentalmentioning
confidence: 99%
“…They present evidence that the incidence of some cancers at Hanford is an order of magnitude greater than expected using conventional extrapolations from the atomic bomb experience. Others (109)(110)(111) have confirmed the findings of increased multiple myelomas and pancreatic cancers, but the absence of myeloid and lymphocytic leukemia, the cancers most expected, and the low statistical power of the study are good reasons for viewing the claims of greater than expected effects with skepticism. A second follow-up study (112) reported that the excess of pancreatic cancers was no longer statistically significant, but that there was an excess of stomach cancers that approached significance; as an aside it is noted that one of the pancreatic cancers is likely to have been a stomach cancer.…”
Section: Cigarettesmentioning
confidence: 90%
“…The mean and variance of radiation doses for the two groups are calculated, and the null hypothesis --that the two groups are the same with respect to cumulative mean dose --is tested by a t-test (5).…”
Section: Standard Analysismentioning
confidence: 99%
“…For radiosensitive tissues, particularly multiple myeloma and leukemia, only multiple myeloma was consistently associated with low level radiation at Hanford (3,5,(7)(8)(9)(11)(12)(13). In the trend tests multiple myeloma continually showed a positive trend, or increases in mortality with increased exposure.…”
Section: Trend Testmentioning
confidence: 99%